Lusty Nationalism: Image and Affect in Alberto Arvelo’s Libertador (2013) - Austin, Elisabeth L. (Revista Canadiense de Estudios Hispánicos, 2020)
Director Alberto Arvelo’s 2013 biopic of Simón Bolívar, Libertador, recasts the general as physically handsome in order to use the actor Édgar Ramírez’s body to enhance the audience’s affective response toward his person, and, by extension, the Venezuelan nation. Curiously, this contemporary film portrayal of Bolívar evokes the use of portraiture during the Virreinato and Independence eras, which stoked nationalistic attachment by synecdoche through using portraits as stand-ins for national heroes such as Bolívar. Libertador thus invokes the past even as it invites spectators of the present to feel something new for its protagonist.